The Effect of Occupational Health Safety (K3) and Work Environment on Employee Performance - Barra Purnama Pradja; Sandi Nasrudin Wibowo (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
The purpose of this study is todetermine whether the variables of occupational health safety (K3) and work environment affect the performance of PT employees. Arteria Daya Mulia Cirebon. The population in this study was 75 karyclouds. The sampling technique in this study used saturated samples. The sampel collected for this study was 75 respondents consisting of permanent employees. This type of research uses quantitative techniques with an associative approach. In this research, data was obtained from research instruments using questionnaires and processed using IBM SPSS 25 software. A value of 1 indicates strongly disagreeing and a value of 5 indicates strongly agreeing. Based on the multiple regression analysis values obtained results of 216,385 > 3.12, it was concluded that occupational health safety (K3) and the work environment had an influence together (simultaneously) positively and significantly on the performance of net B production employees at PT. Arteria Daya Mulia Cirebon by 85.3%. The remaining 14.7% was influenced by other factors outside the study.